Guatemala - Poverty assessment : good performance at low levels - World Bank (World Bank, 2012)
This report is organized into three sections with seven chapters. The first section assesses poverty levels and changes over time within Guatemala and compares both the levels and changes to those of other countries. It summarizes the overall conditions and changes in Guatemala (chapter one); presents the country's poverty profile and analyzes the evolution of poverty over time and space using monetary and non-monetary indicators, population changes and inequality (chapter two); and benchmarks Guatemala's social progress against other countries in the region and the world (chapter three). The second section analyzes social programs and considers how existing policies and programs could improve their impact on poverty. It highlights some of the key features of social programs in education, health, and social assistance (chapter four); and estimates the potential impact of an expansion of a conditional cash transfer program on poverty (chapter five). The third section focuses on the sources of income of the poor. It documents the evolution of the sources of income examines regional specific characteristics that promote or hinder households potentials (chapter six); and carries out a preliminary analysis of shocks and vulnerability influencing household wellbeing covering the impact of hurricane Stan, a potential reduction in remittances, food price increases, and crime and violence (chapter seven).